REPRESENTASI NILAI DHARMA DAN ADHARMA DALAM SATUA I BAWANG TEKEN I KESUNA: LITERATURE REVIEW - Ida Bagus Yoga Swadnyana; I Wayan Sujana; Komang Emaliana Trianita; Ni Kadek Diah Hermayanti; Ni Komang Sri Devikananda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Traditional literature, known as Satua Bali, aims to teach moral principles to the younger generation. This study aims to examine how the values of dharma and adharma are represented in the Satua I bawang teken i kesuna. The objectives of this research were achieved through the application of a qualitative approach and a literature review method. Primary data was derived from the satua text, while secondary data was sourced from scientific journal articles published within the last five years that discuss moral values, character education, and Balinese local wisdom. Intrinsic narrative elements, such as characters, plot, conflict, and symbolism, were used to analyze the content. The results of the study indicate that the character I bawang is honest, diligent, patient, and sincere, while the character I kesuna is envious, greedy, and lazy. The concepts of karmaphala, Tri hita karana, and the teaching of tat twam asi, which exist within Balinese Hindu culture, were used to construct symbolic representations of these two values. In this satua, the conflict between dharma and adharma serves as a medium for social control and character formation. This remains relevant in contemporary education. As a result of this research, Balinese satua has great potential to become an effective platform for teaching character based on local wisdom to the younger generation.